ChemInform Abstract: Two 1‐D Krebs‐Type Heteropolyoxotungstates Based on [X2W21O72Na(OH)2]13‐ (X: SbIII, BiIII) Units. Issue 47 (3rd November 2016) - Li, Hailou; Chang, Shenzhen; Ma, Xing; Liu, Jinglin; Luo, Jie; Zhao, Junwei
Abstract: [Me2 NH2 ]2 Na11 [X2 W21 NaO72 (OH)2 ] ·34H2 O (X: Sb III (I), Bi III (II)) are prepared by a one‐pot self‐assembly of aqueous solutions of Na2 WO4, NaOAc, and Me2 NH2 Cl to which a HCl solution of SbCl3 (or Bi(NO3 )3 and Zr(NO3 )4 for (II)) is added dropwise.